(untitled) - Gil Held (New York, 1995)
Historical development of communications; Development of computational machinery; Role and utilization of terminals and personal computers; Fundamental concepts of data communications; Transmission and equipment basics; Regulation agencies and communications vendors; The communications industry; Common carrier offerings: cost and selection considerations; Interfacing data transmission devices...
Keywords: Data transmission systems